1992
DOI: 10.1002/j.1460-2075.1992.tb05225.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tyrosine-specific protein phosphorylation on the assembly of adherens-type junctions.

Abstract: Adherens‐type junctions (AJs) are major subcellular targets for tyrosine specific protein phosphorylation [Volberg et al. (1991) Cell Regul., 2, 105–120]. Here we report on the apparent effect of such phosphorylation events on the assembly and integrity of AJs. We show that incubation of MDCK cells with potent inhibitors of tyrosine‐specific phosphatases (PTP), namely H2O2 and vanadate, leads to a dramatic increase in AJ‐associated phosphotyrosine which was apparent already within 2–5 min of treatment and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
182
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(196 citation statements)
references
References 52 publications
14
182
0
Order By: Relevance
“…The present results suggest that gap junctions in non-transformed cells might be targets for tyrosine kinases along with other types of cellular junctions and adhesion molecules [44][45][46][47]. The normal content of phosphotyrosine in Cx43 is clearly below the limit of detection.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The present results suggest that gap junctions in non-transformed cells might be targets for tyrosine kinases along with other types of cellular junctions and adhesion molecules [44][45][46][47]. The normal content of phosphotyrosine in Cx43 is clearly below the limit of detection.…”
Section: Discussionmentioning
confidence: 63%
“…Vanadate is a classical protein-tyrosine phosphatase (PTPase) ■"Corresponding author. Fax: (47) 22 93 57 67. E-mail; s.o.mikalsen@labmed.uio.no Abbreviations: GJIC, gap junctional intercellular communication; Cx43, connexin43; SHE, Syrian hamster embryo; PTPase, proteintyrosine phosphatase; Vanadate, orthovanadate; NP, PI, P2, the nonphosphorylated and the major phosphorylated forms of Cx43 A preliminary part of these data was presented at the IV European Congress of Cell Biology, Prague, Czech Republic, 26 June-1 July 1994 [49].…”
Section: Introductionmentioning
confidence: 99%
“…Several nonreceptor PTKs are preferentially associated with the plasma membrane, including members of the src family (Tsukita et al, 1991;Matsuyoshi et al, 1992;Behrens et al, 1993;Hamaguchi et al, 1993). Src transformation increases tyrosine phosphorylation of cell-cell adherens junction proteins and diminishes cadherin-dependent, homophilic adhesion (Matsuyoshi et al, 1992;Volberg et al, 1992;Behrens et al, 1993;Hamaguchi et al, 1993). Interestingly, PTK inhibition with herbimycin A also protects against this loss of intercellular adhesion (Matsuyoshi et al, 1992;Hamaguchi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…PTPs play a crucial role in regulating protein tyrosine phosphorylation of adherens junctions (Volberg et al, 1992;Brady-Kalnay et al, 1995;Fuchs et al, 1996). Receptor PTP activity increases during contact inhibition of cultured cells in vitro (Gaits et al, 1995;Southey et al, 1995;Fuchs et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…4P) was uneven and disrupted. Likewise, immunostaining for tyrosine phosphorylation, an important regulatory event for formation of cell junctions (Volberg et al, 1992), showed that, while follicle cells in wild-type showed a smooth uniform phosphotyrosine staining of the inner and lateral faces (Fig. 4I), those in Hsp60C 1 /Hsp60C 1 chambers showed uneven and irregular staining with missing columnar arrangement (Fig.…”
Section: Cell-cell Adhesion Is Affected In Hsp60c 1 /Hsp60c 1 Egg Chamentioning
confidence: 94%